Study on the optimization of urban passenger traffic structure based on multi-objective linear programming—a case study of Beijing - Li, Yanmei; Lu, Shuangshuang (Environmental science and pollution research international, 2021)
With the increasing number of car trips in cities, energy consumption and environmental pollution have become key issues in urban transportation. In particular, the increasing use of private cars not only leads to more energy consumption and produces more waste gas, but also makes the traffic structure unbalanced. Therefore, it is necessary to establish and optimize the reasonable traffic structure in order to promote the sustainable development of urban traffic. Based on the characteristics of different transportation modes, this paper proposes a multi-objective optimization model that maximizes transportation utility, minimizes ecological impact, and minimizes generalized cost. The ideal point method, linear weighting method, and hierarchical sequence method were used to solve and compare the model. It has been concluded that the ideal point method is more suitable for the research of this paper and can be applied to optimize the traffic structure of Beijing. Through example analysis, the optimized urban passenger traffic turnover and sharing rate are more scientific and reasonable, which verifies the feasibility of the model. This model not only guarantees the interests of passengers and reduces carbon emissions, it also maximizes the utility of urban traffic and the lowest generalized cost. It reflects the concept of sustainable development of urban transportation. Finally, we are able to make reasonable suggestions to relevant departments based on the optimization results.